2016
DOI: 10.1007/s11673-016-9708-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ethical Imperative to Move to a Seven-Day Care Model

Abstract: Whilst the nature of human illness is not determined by time of day or day of week, we currently structure health service delivery around a five-day delivery model. At least one country is endeavouring to develop a systems-based approach to planning a transition from five- to seven-day healthcare delivery models, and some services are independently instituting program reorganization to achieve these ends as research, amongst other things, highlights increased mortality and morbidity for weekend and after-hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Seven-day provision of consistent, high-quality urgent and emergency care settings is an international research and policy priority 1–6. This is motivated by 15 years of attention placed on the enigmatic ‘weekend effect’ and other temporal variations,7 scrutinising mortality and other outcomes for those admitted at the weekend compared with during the week 5 8–14.…”
Section: Introductionmentioning
confidence: 99%
“…Seven-day provision of consistent, high-quality urgent and emergency care settings is an international research and policy priority 1–6. This is motivated by 15 years of attention placed on the enigmatic ‘weekend effect’ and other temporal variations,7 scrutinising mortality and other outcomes for those admitted at the weekend compared with during the week 5 8–14.…”
Section: Introductionmentioning
confidence: 99%
“…It is now recognised that temporal variation results, at least in part, from delivery models of care and the cultural values of the health-care sector, enshrined in everyday practice, funding models, staffing practices and wider policies. 29 Recent research, such as the High-Intensity Specialist-Led Acute Care study, 30,31 have taken this approach to examine the intensity of specialist-led care in emergency medical admissions, focusing particularly on the organisation and delivery of care, and medical staffing. 30,31 In the case of urgent stroke care, recent studies have shown that temporal variation in mortality is now decreasing, 32,33 including in London's hyperacute stroke unit (HASU) model.…”
Section: Chapter 1 Contextmentioning
confidence: 99%
“…Seven-day provision of consistent, high-quality, urgent and emergency care settings is an international research and policy priority. 9,11,29,61,78,79 This has motivated 15 years of attention on the 'weekend effect' and other temporal variations, 22 scrutinising mortality and other outcomes for those admitted at the weekend compared with those admitted during the week. 6,7,9,31,[80][81][82][83] Varying features that may explain differential outcomes include staffing levels 31 and patient mix, 25 leading to widespread interest in studying weekend organisational features.…”
Section: What This Analysis Adds Introductionmentioning
confidence: 99%
“…Although EDs operate much closer to a 24/7 model of care, 12,13 they exist within the context of the broader hospital which typically does not. 14 Patient case-mix (i.e. sociodemographic or case-mix characteristics) and hospital staffing differences between within-and after-hours periods are of significant interest when considering any potential differences in outcome.…”
Section: Importancementioning
confidence: 99%
“…Investigations of outcomes for after‐hours healthcare delivery have typically focused on inpatient admissions. Although EDs operate much closer to a 24/7 model of care, 12,13 they exist within the context of the broader hospital which typically does not 14 . Patient case‐mix (i.e.…”
Section: Introductionmentioning
confidence: 99%